Association of the Systemic Lupus International Collaborating Clinics Frailty Index and Damage Accrual in Longstanding Systemic Lupus Erythematosus. Issue 3 (31st October 2022) - Lima, Kaitlin; Legge, Alexandra; Hanly, John G.; Lee, Jungwha; Song, Jing; Chung, Anh; Ramsey‐Goldman, Rosalind
Abstract : Objective: To externally validate the Systemic Lupus International Collaborating Clinics Frailty Index (SLICC‐FI) in a prevalent systemic lupus erythematosus (SLE) cohort and to assess the ability of the SLICC‐FI to predict organ damage accrual among individuals with longstanding SLE. Methods: This was a secondary analysis of data from the Study of Lupus Vascular and Bone Long‐Term Endpoints (SOLVABLE) cohort, which consists of adult women from the Chicago Lupus Database who met the 1997 revised American College of Rheumatology (ACR) classification criteria for SLE. There were 185 patients with SLE enrolled, of whom 149 patients were included in a 5‐year follow‐up analysis. The SLICC‐FI and SLICC/ACR Damage Index (SDI) scores were calculated at baseline and 5‐year follow‐up. Unadjusted and adjusted logistic regression models estimated the association of baseline SLICC‐FI scores (per 0.05 increase) with damage accrual at 5‐year follow‐up. Results: At enrollment the mean ± SD age of the 149 patients was 43.30 ± 10.15 years, the mean ± SD disease duration was 11.93 ± 8.46 years, and the mean ± SD SDI score was 1.64 ± 1.83. At baseline, the mean ± SD SLICC‐FI score was 0.18 ± 0.08, and 36% of participants were categorized as frail (SLICC‐FI score >0.21). In a model adjusted for age, race, and disease duration, each 0.05‐unit increase in the baseline SLICC‐FI score was associated with 28% higher odds of subsequent damage accrual (odds ratio 1.28, 95% confidence interval 1.01–1.63). Conclusion: In a prevalent cohort of women with established SLE, higher baseline SLICC‐FI scores were associated with a higher risk of subsequent damage accrual at 5‐year follow‐up.